MENELUSURI KEBAHAGIAN: ANALISIS MENDALAM TENTANG 'THE BOOK OF IKIGAI' DALAM BINGKAI SUBJECTIVE WELLBEING - Putri, Mita Tiara Kharisma; Oktasari, Maria; Azzahra, Nada Aulia; Haikal, Ahmad; Azzahra, Shafira; Fuhansyah, Dina Ramadhani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This study discusses the Japanese concept of Ikigai and its relationship with subjective well-being. The concept of Ikigai has five main aspects, namely starting small, freeing yourself, harmony and continuity, joy from small things, and being present in the present place and time. This research uses qualitative methods and analyzes the content of